2008
DOI: 10.1021/ja8069743
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure of Metal−Organic Framework Grown on Self-Assembled Monolayers Revealed by High-Resolution Atomic Force Microscopy

Abstract: The surface structure of an individual metal-organic framework (MOF) microcrystal grown on a functionalized surface has been successfully investigated for the first time in air and vacuum using high-resolution atomic force microscopy. Moreover, this detailed surface analysis has been utilized to optimize the MOF formation procedure to obtain a defect-free surface structure. Comparison of obtained data with recent microscopic studies performed on the same MOF crystal but grown by a conventional procedure clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 17 publications
2
35
0
4
Order By: Relevance
“…The evolution in surface growth of HKUST-1 using ex situ atomic force microscopy (AFM) on the [111] facets of these octahedral crystals revealed crystal growth in steps of height of 1.5 ± 0.1 nm [76,77]. The application of low temperature ambient pressure synthesis routes have allowed in situ AFM experiments on the same [111] plane gaining deeper insight into crystal growth at the nanoscale [78].…”
Section: Crystal Surface Structurementioning
confidence: 99%
“…The evolution in surface growth of HKUST-1 using ex situ atomic force microscopy (AFM) on the [111] facets of these octahedral crystals revealed crystal growth in steps of height of 1.5 ± 0.1 nm [76,77]. The application of low temperature ambient pressure synthesis routes have allowed in situ AFM experiments on the same [111] plane gaining deeper insight into crystal growth at the nanoscale [78].…”
Section: Crystal Surface Structurementioning
confidence: 99%
“…[13] In case of MOFs, of course, growth needs to be studied at the solid-liquid interface. [14] Although using MOF single crystals for growth studies is in principle possible, [15] this is a rather difficult approach since the handling of the micrometer-sized single crystals is experimentally challenging. To date studies in ultrahigh vacuum (UHV) using atomic force microscopy (AFM) have been reported, [16] but it will be difficult to achieve such high resolution in a liquid.…”
mentioning
confidence: 99%
“…[13] Natürlich müsste man im Fall von MOFs anstelle der für diese Materialien normalerweise eingesetzten Gasphasenabscheidung das Wachstum an einer Fest-flüssig-Grenzschicht betrachten. [14] Obwohl die Verwendung von MOF-Einkristallen für Wachstumsstudien prinzipiell möglich ist, [15] ist dies ein vergleichsweise schwieriges Verfahren, da die experimentelle Handhabung der mikrometergroßen MOF-Kristallite eine Herausforderung darstellt. Rasterkraftmikroskopische Studien (AFM) sind zwar in einem Fall schon im UHV ausgeführt worden, [16] es wird aber schwer sein, ähnlich hohe Auflösungen in einer Flüssigkeit zu erzielen.…”
unclassified
“…[14] Obwohl die Verwendung von MOF-Einkristallen für Wachstumsstudien prinzipiell möglich ist, [15] ist dies ein vergleichsweise schwieriges Verfahren, da die experimentelle Handhabung der mikrometergroßen MOF-Kristallite eine Herausforderung darstellt. Rasterkraftmikroskopische Studien (AFM) sind zwar in einem Fall schon im UHV ausgeführt worden, [16] es wird aber schwer sein, ähnlich hohe Auflösungen in einer Flüssigkeit zu erzielen. Hier wollen wir nun die Ergebnisse eines anderen Ansatzes vorstellen.…”
unclassified